An international review of laser Doppler vibrometry: Making light work of vibration measurement. (December 2017) - Rothberg, S.J.; Allen, M.S.; Castellini, P.; Di Maio, D.; Dirckx, J.J.J.; Ewins, D.J.; Halkon, B.J.; Muyshondt, P.; Paone, N.; Ryan, T.; Steger, H.; Tomasini, E.P.; et al.
Abstract: In 1964, just a few years after the invention of the laser, a fluid velocity measurement based on the frequency shift of scattered light was made and the laser Doppler technique was born. This comprehensive review paper charts advances in the development and applications of laser Doppler vibrometry (LDV) since those first pioneering experiments. Consideration is first given to the challenges that continue to be posed by laser speckle. Scanning LDV is introduced and its significant influence in the field of experimental modal analysis described. Applications in structural health monitoring and MEMS serve to demonstrate LDV's applicability on structures of all sizes. Rotor vibrations and hearing are explored as examples of the classic applications. Applications in acoustics recognise the versatility of LDV as demonstrated by visualisation of sound fields. The paper concludes with thoughts on future developments, using examples of new multi-component and multi-channel instruments. Highlights: A historical review of laser Doppler vibrometry (LDV) is presented. Such a comprehensive review of LDV has not been authored before. Single beam, parallel beam, multi-beam, scanning and tracking systems are considered. Diverse applications are described e.g. modal analysis, structural health, MEMS, rotor vibration, hearing and acoustics. The paper ends with thoughts on future developments.